The synthesis of new bola-amphiphile TPEs and the comparison of current transformer mechanism and structural properties for Al/Bis(HCTA)-TPE/p-Si and Al/Bis(HCOA)-TPE/p-Si heterojunctions. (1st September 2019) - Sevgili, Ömer; Lafzi, Ferruh; Karabulut, Abdulkerim; Orak, İkram; Bayındır, Sinan
Abstract: In this study, the new bola-amphiphile tetraphenylethylene derivatives Bis(HCTA)-TPE and Bis(HCOA)-TPE were synthesized to use in device application by a green approach. Al/organic layer/p-Si heterojunctions were fabricated by the usage of Bis(HCTA)-TPE and Bis(HCOA)-TPE organic interfacial layers. The mentioned organic layers were coated on the polished side of silicon wafer using the spin coating method. The surface and morphological analyses of materials coated on silicon substrate were investigated by using atomic force microscopy (AFM) and scanning electron microscopy (SEM) images. Besides, the electrical characteristics of fabricated heterojunctions were examined by the use of current-voltage ( I–V ) and current-time ( I-t ) measurements and compared with each other. I–V characteristics were investigated under various illumination conditions, and also the behavior of these characteristics against changing temperature conditions has been determined. At the same time, transient photocurrent measurements were performed to determine the photoresponse behaviors. The results show that the fabricated device with Bis(HCTA)-TPE organic interfacial layer exhibits better electrical characteristics than the Bis(HCOA)-TPE organic layer. The other result of this experiment is that the fabricated devices could be used in optoelectronic and photovoltaic applications. Graphical abstract: Image 1